A vida e a norma como valores supremos do ser humano: a previsão constitucional do biodireito - Rocha, Renata da (2012)
The circumstances brought about during the last quarter of the 20th century, particularly as far as the advances of medical science are concerned and the association that took place with other incipient areas of knowledge, such as genetic engineering and molecular biology, gave rise to Biomedicine. In this respect, countless possibilities came about such as: artificial insemination, in vitro fertilization, stem cell research - embryonic and adult -, genetic engineering, pre-implantation genetic diagnosis, therapeutic cloning, gene therapy, eugenics, pain control and lengthening of human life. These possibilities necessarily lead to choices that drift towards ethical dilemmas and as such to legal consequences. Should we allow genetic test results decide the future of an embryo? Who will eventually decide which tests should be carried out? The parents, the doctor, the State? Will there be any chance of us experiencing a new eugenics? Will it be possible, in the future, to hold legally responsible those who suffered genetic modification against their will? Bioethics has already started to introduce ethical norms to guide scientists so that the inherent risks of these practices can be minimized. However, it is already possible to foresee the need for the establishment of legal norms providing safe limits for the advance of Biomedicine. This is therefore the main objective of the current study. With this in mind, the notion that a new branch of the existing Law be developed has been put forward. A fourth dimension system named Biolaw which will address above all, the protection of the human life process, initiating at conception and ending at death, safeguarding the dignity of the human being ontologically speaking and not only in the civil sense of the term. These two values represent the theoretical foundation, the anthropological base, linked to the human vital process and ontological dimension, related to the dignity of the human being, upon which Biolaw should be constructed. For this reason, the recognition of the formal and material fundamentality of its norms requires legal response: the constitutional introduction of legal norms through an amending act to the Brazilian Constitution